Ketika Pekerja Bank Memilih Hijrah: Perubahan Karier dan Implikasinya terhadap Ekonomi Keluarga - Damero, Lian; Luqman; Syahbudi (JOM, 2024)
The increasing phenomenon of bank employees choosing to resign to avoid riba presents new challenges, particularly in terms of family economic resilience. Therefore, careful planning and selection of alternative jobs after hijrah need to be considered to ensure the family's economic needs are met. This study aims to analyze the background of X-Bank's decision to undergo hijrah and the changes in their career choices afterward. This research employs a descriptive qualitative method with a phenomenological approach. Data collection techniques include in-depth interviews with former bank employees who have undergone hijrah, documentation of their experiences before and after hijrah, and observations of their economic conditions after transitioning to new professions. The collected data were analyzed through data reduction, data presentation, and conclusion drawing to gain a deep understanding of the studied phenomenon. The findings indicate that X-Bank's decision to undergo hijrah was influenced not only by religious factors but also by work pressure and an unhealthy work environment. After hijrah, X-Bank tends to choose entrepreneurship as a profession. In terms of economic resilience, family economic conditions improved and became more stable after transitioning to a new profession.